Analisis Efektivitas Metode Forecasting Terhadap Permintaan Produk PT Arara Abadi Perawang - Hengki Yulianto; Samsir '; Iwan Nauly Daulay (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this study was to examine the effectiveness of methods of forecasting the demand for the product at Arara Abadi. The data were obtained by direct observation company the research object, namely PT. Arara Abadi and interviews with the parties that the leadership of the company and some of the workers. Based on the results of forecasting method moving average (moving average) single moving average is done within 3 months and 5 months. Forecasting using a single 3-month moving average forecasting results did not correspond to reality. It is also the case with forecasting using a single 3-month moving average also does not correspond to reality. Forecasting results using weighted moving average (weighted moving average) is known demand for wood logs and chip was highest in August 2012. Through the method of forecasting with exponential smoothing (exponential smoothing) is performed with α = 0.1 and 0.5 are known forecasting results are not in accordance with reality and there are still errors. Exponential smoothing method of forecasting the trend (exponential smoothing with trend) known to forecast the results do not match with reality and there are still errors. Concluded that the appropriate forecasting method for forecasting the demand for wood logs and chips at PT. Arara Abadi is a method of moving average (moving average) , especially single 5 monthly moving average for forecasting is done by the moving average method has the smallest absolute error than the method of forecasting other.Keywords:Effectiveness, Single Moving Average